Word stemming for Malay document based retrieval system using Latent Semantic indexing technique / Muhd Ruzlan Kamaruzaman - Kamaruzaman, Muhd Ruzlan (2010)
Documents retrieval in Information Retrieval Systems (IRS) is generally about understanding of information in the documents concern. The more the system able to understand the contents of documents the more effective will be the retrieval outcomes. But understanding of the contents is a very complex task. Conventional IRS applies algorithms that can only approximate the meaning of document contents through keywords approach using Latent Semantic indexing. In information retrieval, a text operation is called indexing is applied to the documents need to be retrieved, in order to aid with the retrieval process by making it easier to search through the documents available.